Perancangan DashPerancangan Dashboard Monitoring Status Gizi Balita di Puskesmas Sukanagalihoard Monitoring Status Gizi Balita di Puskesmas Sukangalih - Yusuf Alfiansyah, Fakhri; Arisandi, Desi (STMIK Banjarbaru, 2023)
Monitoring the nutritional status of toddlers is a crucial component in ensuring healthy growth and development of children. Nevertheless, the monitoring of nutritional status at Puskesmas Sukanagalih faces challenges in effective data visualization and integration, hindering rapid and accurate data-driven decision-making. This research aims to enhance the effectiveness of the nutrition program at Puskesmas Sukanagalih by designing an interactive dashboard built using the Business Intelligence Roadmap methodology. The designed dashboard based on data of toddler nutritional status measurements, collected from January 2018 to August 2023, to illustrate the distribution of nutritional status related to demographic and geographic variables. Through the implementation of a star schema and Extract, Transform, Load (ETL) process, data is integrated and processed to create efficient and informative visualizations. Functional testing results using black-box testing indicate dashboard's success providing relevant and interactive data visualizations, supporting the modification date function for analyzing toddler nutrition trends over specific periods. Keywords: Toddlers; Nutrition Status; Dashboard; Business Intelligence Roadmap; Star Schema.AbstrakPemantauan status gizi balita adalah komponen penting dalam menjamin pertumbuhan dan perkembangan anak yang sehat. Meskipun demikian, Pemantauan status gizi balita di Puskesmas Sukanagalih menghadapi tantangan dalam visualisasi dan integrasi data yang efektif, menghambat keputusan berbasis data yang cepat dan akurat. Penelitian ini bertujuan untuk mengembangkan efektivitas program gizi di Puskesmas Sukanagalih dengan merancang dashboard interaktif yang dibangun menggunakan metode Business Intelligence Roadmap. Dashboard yang dirancang berbasis data pengukuran status gizi balita, dikumpulkan dari periode Januari 2018 hingga Agustus 2023, untuk mengilustrasikan distribusi status gizi terkait dengan variabel demografis dan geografis. Melalui implementasi star schema dan proses Extract, Transform, Load (ETL), data diintegrasikan dan diproses untuk menciptakan visualisasi yang efisien dan informatif. Hasil pengujian fungsionalitas menggunakan black-box testing menunjukkan keberhasilan dashboard dalam menyediakan visualisasi data yang relevan dan interaktif, mendukung fungsi modifikasi tanggal untuk analisis tren gizi balita pada periode spesifik.Â